A Singular Environment: Featuring a Framework for Integrated Project Management - Reis, Inês; Ribeiro, Pedro (Procedia computer science, 2023)
There's always been a need to improve everyone's work process to ease the productivity and effectiveness of project management. However, this task entails many mechanisms, which might take a lot of time and cause the main priorities to be overlooked. That's when open-source environment solutions came. This article explores the need for being able to gather all subject changes in scope, time, cost, and quality, among others. For that were explored open-source environments and selected the one that's most suitable for gathering all characteristics, supported by the eight domains of the most recent version of Project Management Body of Knowledge in its 7th version. Furthermore, this environment also intends to stay updated by supporting future trends such as sustainability, agility, risk, requirements, and benefits management. Thereby, this tool gives a singular way of managing projects in a way that improves performance and increases higher success rates by providing accurate information.